Prediction of Neonatal Birth Weight in Obese Women by Presence of Diabetes [29D]. (May 2020) - McCurdy, Rebekah; Gleason, Laura
Abstract : INTRODUCTION: To design a model that will predict neonatal birth weight within obese mothers by diabetic status. METHODS: A secondary data analysis of an RCT (NCT 02909582) was utilized to create a neonatal birth weight prediction model. Women (n=325) with a BMI >35 kg/m 2 from a tertiary academic institution, 2016–2019, were included to estimate the risk of large for gestational age (LGA) infants and neonatal birth weight based on maternal pre-pregnancy BMI and diabetic status. LGA was defined as an infant birth weight >90th percentile. Analysis included Chi-square, t-test, multivariate logistic and linear regression. RESULTS: Mean birthweight did not differ in obese mothers based on diabetic status ( P >.05). The frequency of large for gestational age infants was significantly greater for diabetic mothers (17% vs 7% without diabetes, P =.024). Total pregnancy weight gain (continuous, lbs) (OR 1.03; 95% CI 1.01, 1.05; P =.016) and pre-pregnancy BMI (continuous, OR 1.08; 95% CI 1.01, 1.15; P =.018) were associated with the risk of LGA infants when accounting for demographics (model R2=0.074). The presence of diabetes (RR 146; 95% CI 24, 268; P =.019), total weight gain (lbs) (RR 4; 95% CI 1, 7; P =.015), and gestational age (RR 197; 95% CI 175, 220; P <.001) were associated with neonatal birth weight when accounting for demographics (model R2=0.550). CONCLUSION: These models incorporate the joint effects of maternal obesity and diabetic status in predicting neonatal birthweight, thereby enabling clinicians to counsel their high-risk patients on risk for large for gestational age infants.